Equity Effects of Dietary Nudging Field Experiments: Systematic Review - Schüz, Benjamin; Meyerhof, Hannah; Hilz, Lisa Karla; Mata, Jutta (Frontiers in Public Health, 2021)
Background: Dietary behaviours are among the key modifiable risk factors for non-communicable diseases. Importantly, dietary behaviours vary substantially between groups and individuals with different socioeconomic positions, with more disadvantaged groups and individuals being exposed to more dietary risk factors. The goal of this review is to summarise the existing research on equity effects of dietary nudging interventions. Methods: Systematic review of nudging interventions conducted in a field setting that report an observable indicator of dietary behaviour, include a control group, and report effect sizes stratified by indicators of socioeconomic status as outlined in the PROGRESS-Plus framework. Two databases (scopus, Pubmed) were searched (last search June 2021), and 18 articles with 19 studies (k = 46 equity comparisons) were included. Risk of bias was assessed using the ROBINS-I tool. Due to heterogeneity in equity dimensions and study outcomes, a harvest plot was used to summarise data. Results: The majority of equity comparisons (38 out of 46) were available for cognitive nudges. Most of these (22 out of 38 comparisons) found that cognitive nudges worked equally well in more and less disadvantaged populations; however, in 12 out of the 38 comparisons, they favoured those who were less disadvantaged. Two out of four comparisons on behavioural nudges favoured more disadvantaged persons. Conclusions: The differential effects of dietary nudging interventions in this review can contribute to increases in health inequalities. At the same time, a substantial number of interventions showed no equity effects. Importantly, this review suggests that more research on nudging interventions and health equity is needed. Future interventions should report effect sizes stratified by indicators of social inequality. Systematic Review Registration: PROSPERO (CRD42019137469)